(untitled) (International Journal of Food and Nutritional Sciences, 2025)
To establish a strong multi-stage authentication system for improved security access control, the suggested method combines RFID technology with iris recognition. The system is implemented using MATLAB and Arduino, utilising features extraction, segmentation, preprocessing, eye detection, and classification for iris recognition, among other image processing techniques. Users must undergo RFID authentication when their iris scan is successfully recognised. To achieve dual authentication, they must also provide an RFID card or tag. Assuring a robust and multi-layered authentication mechanism, access is only authorised after successful verification through both biometric (iris) and electronic (RFID) techniques. Securing critical facilities or restricted areas is made possible by merging RFID and iris recognition technologies to provide a more dependable and effective access control system. Furthermore, tools for visualisation are incorporated into to assess the efficiency and precision of the authentication procedure, hence augmenting the system’s dependability in practical situations